The Influence of Professionalism, Locus of Control, Emotional Intelligence and Professional Ethics on BPR Audit Quality with Ambiguity as a Moderator - Dina Safitri; Rohmah, Siti; Salta, Salta (PT FORMOSA CENDEKIA GLOBAL, 2024)
As an independent party, auditors have the opportunity to improve the quality and reliability of company financial reports that are used by stakeholders in making decisions. Against this background, incidents relating to the accounting profession from an audit quality perspective are increasing. Incidents often occur with test objects due to the inspector's incompetence. The loss of public trust in the accounting profession is an indication of the loss of AI's strict internal audit concept and a weak governance system. This research aims to determine how professionalism, locus of control, emotional intelligence, and professional ethics influence audit quality. auditors who participated in this research working in BPR Region III in Cirebon, West Java, were used as respondents. The resulting sample consisted of 49 of the 83 research topics selected to represent BPR researchers. The results show problems with normality, multicollinearity, and autocorrelation in the classical assumption test, which consists of normality, multicollinearity, and heteroscedasticity tests using a one-stage multivariate model. The remainder is influenced by other invisible variables, with a total influence of 0.598 or 59.8%.